(3QSGdI aj MbGFb Yde GdJhMjOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3CeG HYO abO SCdfi HYV eef jfJei Edi Cf GPcQ dg QSGdI eTJedI Ydi MbGFb Yde GdJhMjO s
(3BNQgG (B:s
(3hHGdbUO GdChd ai GdbVGA HGdhgf hEf cGf agPG BNQ GdQSGdI hUdhGJg Ydi eMeO hCdg CLeYjf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds